Declaratoon of indendence 1945 - career value protect the country now - Bùi Quang Huy,; Nguyễn Huy Phong, (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
On September 2, 1945, at Ba Dinh Square, Hanoi capital, President Ho Chi Minh on behalf of the nation and compatriots read the Declaration of Independence giving birth to the Democratic Republic of Vietnam. The Declaration of Independence is brief but contains immortal contents, historical significance, and profound epochal values ​​in the current cause of building and firmly defending the socialist Vietnamese Fatherland.